Transcatheter Arterial Infusion of Autologous CD133+ Cells for Diabetic Peripheral Artery Disease. (14th February 2016) - Zhang, Xiaoping; Lian, Weishuai; Lou, Wensheng; Han, Shilong; Lu, Chenhui; Zuo, Keqiang; Su, Haobo; Xu, Jichong; Cao, Chuanwu; Tang, Tao; Jia, Zhongzhi; Jin, Tao; et al.
Abstract : Microvascular lesion in diabetic peripheral arterial disease (PAD) still cannot be resolved by current surgical and interventional technique. Endothelial cells have the therapeutic potential to cure microvascular lesion. To evaluate the efficacy and immune-regulatory impact of intra-arterial infusion of autologous CD133 + cells, we recruited 53 patients with diabetic PAD (27 of CD133 + group and 26 of control group). CD133 + cells enriched from patients' PB-MNCs were reinfused intra-arterially. The ulcer healing followed up till 18 months was 100% (3/3) in CD133 + group and 60% (3/5) in control group. The amputation rate was 0 (0/27) in CD133 + group and 11.54% (3/26) in control group. Compared with the control group, TcPO2 and ABI showed obvious improvement at 18 months and significant increasing VEGF and decreasing IL-6 level in the CD133 + group within 4 weeks. A reducing trend of proangiogenesis and anti-inflammatory regulation function at 4 weeks after the cells infusion was also found. These results indicated that autologous CD133 + cell treatment can effectively improve the perfusion of morbid limb and exert proangiogenesis and anti-inflammatory immune-regulatory impacts by paracrine on tissue microenvironment. The CD133 + progenitor cell therapy may be repeated at a fixed interval according to cell life span and immune-regulatory function.